Yemen and its Kingdoms in the Torah (Journal of the College of Basic Education, 2024)
Yemen is considered one of the most prominent places in the Arabian Peninsula due to its geographical and cultural status, as it is characterized by a cultural precedence in the societies of the Arabian Peninsula in its ancient times, and it is one of the ancient civilizations such as (Mesopotamia and the civilization of the Nile Valley). It has been covered by many written sources, the first of which is the Torah, which is the historical source. Yemen is considered one of the most prominent places in the Arabian Peninsula due to its geographical and cultural status, as it is characterized by a cultural precedence in the societies of the Arabian Peninsula in its ancient times, and it is one of the ancient civilizations such as (Mesopotamia and the Nile Valley Civilization). It has been covered by many written sources, the first of which is the Torah, which is the historical source. Yemen is considered one of the most prominent places in the Arabian Peninsula due to its geographical and cultural status, as it is characterized by a cultural precedence in the societies of the Arabian Peninsula in its ancient times, and it is one of the ancient civilizations such as (Mesopotamia and the Nile Valley Civilization). It has been covered by many written sources, the first of which is the Torah, which is the historical source.We find within the books of the Torah many texts that refer to Yemen and its ancient kingdoms and to its trade that extended to large areas and regions in the ancient world. We note that these banners are not exaggerating if we say that most or most of them are not devoid of exaggeration, exaggeration, myths, and some falsification. Therefore, we are in In this research, we touched on the most important kingdoms mentioned in the Torah, the most important of those narratives in which Yemen and its kingdoms were mentioned, and the information contained in other sources showing the truth or falsity of what was mentioned in it.